2020
DOI: 10.1039/d0gc01894e
|View full text |Cite|
|
Sign up to set email alerts
|

In situ electrochemical H2 production for efficient and stable power-to-gas electromethanogenesis

Abstract: Bioelectrochemical power-to-gas presents a promising technology for long-term storage of excess renewable energy in the form of methane. The transition of the technology from laboratory to applied scale is currently...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 29 publications
3
45
5
Order By: Relevance
“…Exposure to alkaline pH environments can compromise microbial organisms like M. maripaludis (Schauer and Whitman, 1989). In fact, in a previous study we found slightly increased cell lysis of M. maripaludis cells grown with in situ electrochemically evolved hydrogen (at 1 mA/cm 2 ) compared to cultures supplied with a gaseous mix of H 2 /CO 2 (Kracke et al, 2020).…”
Section: Mechanism Of Efficient H 2 Delivery In Mesmentioning
confidence: 81%
See 2 more Smart Citations
“…Exposure to alkaline pH environments can compromise microbial organisms like M. maripaludis (Schauer and Whitman, 1989). In fact, in a previous study we found slightly increased cell lysis of M. maripaludis cells grown with in situ electrochemically evolved hydrogen (at 1 mA/cm 2 ) compared to cultures supplied with a gaseous mix of H 2 /CO 2 (Kracke et al, 2020).…”
Section: Mechanism Of Efficient H 2 Delivery In Mesmentioning
confidence: 81%
“…The archaeon M. maripaludis was chosen due to its salinity tolerance and its exceptional performance in previous studies ( Kracke et al, 2020 ). M. maripaludis was cultured using chemically defined medium-JD specifically modified for use in bio-electrochemical reactors as reported previously ( Kracke et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Light-independent, lithoautotrophy can fix carbon by relying on chemically provided reducing power. On Mars, this could either directly be electricity through microbial electrosynthesis in bio-electrochemical systems (Moscoviz et al, 2016;Abel et al, 2020;Chen et al, 2020a), or indirectly by means of hydrogen or (organoautotrophically) formate, both of which can also be generated electrochemically (Kracke et al, 2020;Abel and Clark, 2021). Use of other electron donors like, e.g., sulphide, sulphur and iron (II) is theoretically possible, but technically less feasible (crustal materials from Mars are in principle able to support lithotrophic growth (Milojevic et al, 2021), but mining and purifying these in quantities that could support biotechnological processes is likely not viable).…”
Section: From Autotrophy To Heterotrophy-impact On Process Parameters and Complexitymentioning
confidence: 99%
“…Some also present an explosion hazard. Integrated setups can, however, avoid explosive gas mixtures and achieve significant production rates (Kracke et al, 2020;Sahoo et al, 2021). To completely avoid these problems, methane could be further converted to methanol (Zakaria and Kamarudin, 2016;Latimer et al, 2018)-albeit poor conversion efficiency is a century old unsolved problem.…”
Section: From Autotrophy To Heterotrophy-impact On Process Parameters and Complexitymentioning
confidence: 99%